2006
DOI: 10.1271/bbb.70.551
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Pure Mannan fromOncidium(cv.Gower Ramsey) Current Pseudobulb during Initial Inflorescence Development

Abstract: A water-soluble and neutral polysaccharide was extracted from the current pseudobulbs of Oncidium "Gower Ramsey" during the early inflorescence stage (flower stalk less than 4 cm) by hot water, precipitated with ethanol, and purified with an anion exchanger. From the data of monosaccharide composition and linkage and anomeric configuration analyses, the polysaccharide was identified as a linear beta-1-->4 linked mannan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Mannan polysaccharides are also found in orchids. For example, a pure mannan polysaccharide was extracted from the pseudobulbs of Oncidium ( Wang et al, 2006 ), and glucomannans were found in Dendrobium species such as D . huoshanense and D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannan polysaccharides are also found in orchids. For example, a pure mannan polysaccharide was extracted from the pseudobulbs of Oncidium ( Wang et al, 2006 ), and glucomannans were found in Dendrobium species such as D . huoshanense and D .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pure mannan is also found in the Orchidaceae , such as Oncidium (cv. ‘Gower Ramsey’; Wang et al, 2006 ). Glucomannans found in seeds contain a β-(1,4)-linked D -mannose backbone and β-(1,4)-linked D -glucose residues at different ratios ( Ishrud et al, 2001 ), and exist widely in the vegetative tissues of members of the Liliaceae , Araceae and Orchidaceae ( Meier and Reid, 1982 ).…”
Section: Introductionmentioning
confidence: 99%
“…Buckeridge, unpublished data). There is at least one report of the presence of pure mannan in pseudobulbs of an orchid, Oncidium (Wang et al, 2006). However, it is likely that the polymer is acetylated, as it is soluble upon extraction with hot water.…”
mentioning
confidence: 99%
“…In China, for Oncidium ascendens, researchers have identified a similar traditional therapeutic application to the one documented in Veracruz, i.e., treating inflammation and lacerations of the body [49]. Although studies detected inhibition of cancer cell lines proliferation due to stilbenoids and 1,4-β-mannan in this species [25,26], this action does not explain the efficacy of its traditional therapeutic application.…”
Section: As Far As Their Ethnobotany Villagers Usementioning
confidence: 99%